Spatiotemporal monitoring of surface soil moisture using optical remote sensing data: a case study in a semi-arid area. Issue 3 (1st September 2020) - Khellouk, Rida; Barakat, Ahmed; Boudhar, Abdelghani; Hadria, Rachid; Lionboui, Hayat; El Jazouli, Aafaf; Rais, Jamila; El Baghdadi, Mohamed; Benabdelouahab, Tarik
ABSTRACT: Surface soil moisture content (SSMC) monitoring constitutes an important parameter to estimate crop water requirements, especially in arid and semi-arid areas. Remote sensing became a useful tool for estimating SSMC. Two approaches were applied for monitoring the SSMC during the 2013/14 cropping season in the irrigated perimeter of Tadla (Morocco) using multispectral bands of Landsat-8 OLI images. The first approach examined the potential of visible and short-wave infrared drought index (VSDI), normalized multi-band drought index (NMDI) and short-wave infrared water stress index (SIWSI), to retrieve SSMC. The second approach attempted to develop a new SSMC model based on evaluation of the correlations between multispectral bands and measured SSMC using a stepwise multiple regression analysis. Results showed that the established model is highly correlated with the measured SSMC at all crop growth stages with R 2 of 0.87, 0.85 and 0.89, for bare soil, partially covered and entirely covered by vegetation, respectively.